Pengaruh Metode Cooperative Script Terhadap Kemampuan Membaca Pemahaman Siswa Kelas V SDN Ngudirejo 1 Jombang - Rofiki, Moch Ainur; Rochmania, Desty Dwi (Prodi Pendidikan Guru Sekolah Dasar, 2024)
This study aims to determine the effect of the Cooperative Script learning model on fifth-grade students at SDN Ngudirejo 1 Jombang's ability to read and comprehend Indonesian language subjects. This study employed a one-group, pretest-posttest research design. The sample size for this study was 28 students. This research instrument consists of a pre-test learning outcomes test and a post-test learning outcomes test. Construct validity is used to determine test validity. Expert judgment can be used to evaluate construct validity. In this particular instance. After testing the hypothesis, it is obtained by searching for t count = 13.876 and t table = 2.042, followed by searching for t count > t table, or 13.876 > 2.042. The conclusion is therefore that H 0 is rejected and H 1 is accepted. Therefore, it can be concluded that the Cooperative Script model has an effect on Indonesian learning outcomes. While internal and external factors contribute to the lack of student learning outcomes.